(untitled) (Journal of the College of Basic Education, 2023)
Self-development is present in human instinct, and it is not a matter of vain or idle talk, but on the contrary it is an important factor for its advancement, integration and attainment of happiness. The path is specific and his notice that it is a long and far road so that he muster all his strength to fold this path and move towards the desired goal, and this gratification and direction towards the goal can only be achieved through a full and conscious association with the principle of existence and the human succession to the earth.